EPISTEMOLOGI KEILMUAN HUKUM ISLAM (Sebuah Tawaran Konsep Alternatif) - Idri Shaffat (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2010)
This article tries to explain about the study ofepistemological approach to the science of Islamic law,describing the definition of Islamic law, the analyticalmethods of Islamic law science, and the procedures toanalyze the study of Islamic law science. The analyticalmethods of Islamic law science elucidated in this article arein accordance with deductive-coherence method, inductivecorrespondencemethod, phenomenological method, as wellas functional-structural method. While the procedures toanalyze the study of Islamic law science conducted withthree approach that are taxonomy analysis, competencyanalysis, and information processing. Through the analyticalmethods and the procedures of the study of Islamic lawscience, it is expected that the science of Islamic lawepistemologically can be developed as long as the growth ofscience and technology.